The pattern of intramural veins of the left ventricle of the human heart. - Farrer-Brown, G (1975)
A detailed injection, microradiographic, and histological necropsy study of 18 hearts showed that the pattern of myocardial veins differed from the arterial pattern. In "normal" hearts, large drainage veins began in the subendocardial zone and coursed fairly directly towards the epicardium, maintaining a comparatively even calibre throughout. Smaller, but similar, drainage veins also begain in the middle of the myocardial wall. In the outer myocardium small groups of these vessels converged to form a single vein which then entered, almost at right angles, the pericardial veins. In general, small veins within the myocardium entered directly into the large drainage veins without any extensive intermediate sized venous network. In "abnormal" hearts with left ventricular hypertrophy the myocardial veins appeared basically normal but were more widely separated and consequently overall less dense on microradiography. Interruption of main drainage veins and loss of normal pattern were seen in areas of myocardial fibrosis associated with coronary artery disease. In a heart with severe generalized coronary artery atheroma the normal pattern in the inner half of the wall was replaced by a "plexus" of small veins in which the majority of vessels coursed circumferentially. The possible significance of both the normal and abnormal vein pattern is discussed.